Chitinase 3‐like 1 deficiency ameliorates liver fibrosis by promoting hepatic macrophage apoptosis. Issue 11 (12th July 2019) - Higashiyama, Masaaki; Tomita, Kengo; Sugihara, Nao; Nakashima, Hiroyuki; Furuhashi, Hirotaka; Nishikawa, Makoto; Inaba, Kenichi; Wada, Akinori; Horiuchi, Kazuki; Hanawa, Yoshinori; Shibuya, Naoki; Kurihara, Chie; et al.
Abstract : Aim: Chitinase 3‐like 1 (CHI3L1), an 18‐glycosyl hydrolase‐related molecule, is a member of the enzymatically inactive chitinase‐like protein family. Serum levels of CHI3L1 are strongly correlated with hepatic fibrosis progression during many liver diseases. Therefore, this protein could be involved in the development of hepatic fibrosis pathology; however, its role has not been elucidated. We aimed to elucidate its role in the pathophysiology of liver fibrosis. Methods: Chitinase 3‐like 1‐deficient ( Chi3l1 −/− ) mice were given carbon tetrachloride twice per week for 4 weeks or fed a methionine choline‐deficient diet for 12 weeks to generate mouse liver fibrosis models. Human fibrotic liver tissues were also examined immunohistochemically. Results: In human and mouse fibrotic livers, CHI3L1 expression was mainly localized to hepatic macrophages, and the intrahepatic accumulation of CHI3L1 + macrophages was significantly enhanced compared to that in control livers. In the two mouse models, hepatic fibrosis was significantly ameliorated in Chi3l1 −/− mice compared to that in wild‐type mice, which was dependent on hepatic macrophages. The accumulation and activation of hepatic macrophages was also significantly suppressed in Chi3l1 −/− mice compared to that in wild‐type mice. Furthermore, apoptotic hepatic macrophages were significantly increased in Chi3l1 −/− mice. Chitinase 3‐like 1 was found to inhibit hepatic macrophage apoptosis by suppressing Fas expression and activating Akt signaling in an autocrine manner, which resulted in hepatic macrophage accumulation and activation, exaggerating liver fibrosis. Conclusions: Chitinase 3‐like 1 exacerbates liver fibrosis progression by suppressing apoptosis in hepatic macrophages. Therefore, this might be a potential therapeutic target for the treatment of liver fibrosis.